2020
DOI: 10.1021/acs.est.0c01640
|View full text |Cite
|
Sign up to set email alerts
|

Per- and Polyfluoroalkyl-Contaminated Freshwater Impacts Adjacent Riparian Food Webs

Abstract: The occurrence of per-and polyfluoroalkyl substances (PFASs) in aquatic ecosystems is a global concern because of their persistence, potential bioaccumulation, and toxicity. In this study, we investigated a PFAS-contaminated pond in Sweden to assess the cross-boundary transfer of PFASs from the aquatic environment to the riparian zone via emergent aquatic insects. Aquatic and terrestrial invertebrates, surface water, sediments, soils, and plants were analyzed for 24 PFASs including branched isomers. Stable iso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
39
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(45 citation statements)
references
References 52 publications
5
39
1
Order By: Relevance
“… 33 However, the biomass of emergent aquatic insects collected in that study was not sufficient for quantification of PFAS transferred from water to land. 33 Here, we extend this concept by providing quantitative data on PFAS and explore biodriven transport based on different scenarios for three other sites of varying size, productivity, and contamination extent. To do this, we collected a comprehensive set of samples in 2017 and in 2018, in a PFAS-affected area in Sweden.…”
Section: Introductionmentioning
confidence: 80%
See 2 more Smart Citations
“… 33 However, the biomass of emergent aquatic insects collected in that study was not sufficient for quantification of PFAS transferred from water to land. 33 Here, we extend this concept by providing quantitative data on PFAS and explore biodriven transport based on different scenarios for three other sites of varying size, productivity, and contamination extent. To do this, we collected a comprehensive set of samples in 2017 and in 2018, in a PFAS-affected area in Sweden.…”
Section: Introductionmentioning
confidence: 80%
“… 30 32 In a previous study, we investigated a pond contaminated by aqueous film forming foam (AFFF), and found high concentrations of 24 PFAS in aquatic invertebrates, including emergent aquatic insects, such as adult dragonflies. 33 Hence, terrestrial consumers feeding on emergent aquatic insects from PFAS-contaminated systems could be exposed to PFAS via predation. 33 However, the biomass of emergent aquatic insects collected in that study was not sufficient for quantification of PFAS transferred from water to land.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additional studies on effects of microplastics on terrestrial food web stability, critical ecological processes (e.g., biogeochemical cycles and pollination) and interactions with other anthropogenic stressors must be conducted. Other contaminants, for example, dichlorodiphenyltrichloroethane (DDT; Colborn et al, 1993), per-and polyfluoroalkyl substances (PFAS; Koch et al, 2020) and antibiotics (Ferri et al, 2017) that share similar characteristics as microplastics (i.e., high persistency and widespread presence in the environment) have caused unexpected ecosystem responses including the near extinction of iconic predatory bird species (ospreys and bald eagles; Wiemeyer et al, 1975Wiemeyer et al, , 1984 and even put human health at risk (Fry, 1995;Sunderland et al, 2019). Unlike other chemical contaminants, microplastics have unique properties: make up of diverse polymers, broad size ranges including the nano scale (<0.1 µm), vary in shape and contain diverse chemical additives (Rochman et al, 2019), which increase their likelihood to impact ecosystems and cause ecological surprises.…”
Section: Introductionmentioning
confidence: 99%
“…By virtue of their unique chemical structure, conferring exceptional thermal and chemical stability in addition to water repellence and tensioactive properties, PFAS have been used in a variety of industrial processes and consumer products including firefighting foams, textiles, anti-adherent coatings, food packaging, cosmetics and paints (4). Once released into the environment, these substances are recalcitrant to degradation processes, can migrate towards distant sites and tend to bioaccumulate into living organisms, ultimately entering into the food webs of different ecosystems (5,6). While many efforts have been made to define the toxicological effects of PFAS on susceptible human subpopulations, our knowledge is still limited to few individual substances such as perfluorooctane sulfonic acid (PFOS) and perfluorooctanoic acid (PFOA), which, despite having been phased out by the major producers, are still largely present in the environmental media across the globe (1,7).…”
Section: Introductionmentioning
confidence: 99%